Biomass and elemental concentrations of 22 rice cultivars grown under alternate wetting and drying conditions at three field sites in Bangladesh. (15th June 2017) - Norton, Gareth J.; Travis, Anthony J.; Danku, John M. C.; Salt, David E.; Hossain, Mahmud; Islam, Md. Rafiqul; Price, Adam H.
Abstract: As the global population grows, demand on food production will also rise. For rice, one limiting factor effecting production could be availability of fresh water, hence adoption of techniques that decrease water usage while maintaining or increasing crop yield are needed. Alternative wetting and drying (AWD) is one of these techniques. AWD is a method by which the level of water within a rice field cycles between being flooded and nonflooded during the growth period of the rice crop. The degree to which AWD affects cultivars differently has not been adequately addressed to date. In this study, 22 rice cultivars, mostly landraces of the aus subpopulation, plus some popular improved indica cultivars from Bangladesh, were tested for their response to AWD across three different field sites in Bangladesh. Grain and shoot elemental concentrations were determined at harvest. Overall, AWD slightly increased grain mass and harvest index compared to plants grown under continually flooded (CF) conditions. Plants grown under AWD had decreased concentrations of nitrogen in their straw compared to plants grown under CF. The concentration of elements in the grain were also affected when plants were grown under AWD compared to CF: Nickel, copper, cadmium and iron increased, but sodium, potassium, calcium, cobalt, phosphorus, molybdenum and arsenic decreased in the grains of plants grown under AWD. However, there was some variation in these patterns across different sites. Analysis of variance revealed no significant cultivar × treatment interaction, or site × cultivar × treatment interaction, for any of the plant mass traits. Of the elements analyzed, only grain cadmium concentrations were significantly affected by treatment × cultivar interactions. These data suggest that there is no genetic adaptation amongst the cultivars screened for response to AWD, except for grain cadmium concentration and imply that breeding specifically for AWD is not needed. Abstract : The rice cultivation technique, that is, alternate wetting and drying (AWD) can be used to decrease the volume of water applied to rice during cultivation. In this study, 22 cultivars were tested for adaptation to AWD. Overall, the results indicate that cultivars that perform well under continuously flooded cultivation also perform well under AWD.